Immobilized enzyme reactors in HPLC and its application in inhibitor screening: A review - Si-Meng Fang; Hai-Na Wang; Zhong-Xi Zhao; Wei-Hong Wang (Elsevier, 2012)
This paper sets out to summarize the literatures based on immobilized enzyme bio-chromatography and its application in inhibitors screening in the last decade. In order to screen enzyme inhibitors from a mass of compounds in preliminary screening, multi-pore materials with good biocompatibility are used for the supports of immobilizing enzymes, and then the immobilized enzyme reactor applied as the immobilized enzyme stationary phase in HPLC. Therefore, a technology platform of high throughput screening is gradually established to screen the enzyme inhibitors as new anti-tumor drugs. Here, we briefly summarize the selective methods of supports, immobilization techniques, co-immobilized enzymes system and the screening model. Keywords: Immobilized enzyme reactors (IMERs), Molecular bio-chromatography, Screening enzyme inhibitors